Psychological Support Model Post-Rehabilitation for Child Drug Addicts in Relation to Child Protection Principles - I Gusti Ayu Dilla Susmita Dewi; Ni Gusti Agung Ayu Mas Tri Wulandari (Green Publisher Indonesia, 2025)
Child drug addiction has emerged as a significant global public health and legal challenge, with an estimated 35 million people worldwide suffering from drug use disorders, including a growing number of children and adolescents. The lack of comprehensive post-rehabilitation support systems for child drug addicts represents a critical gap in child protection frameworks, particularly in ensuring sustainable recovery and preventing recurrence. This [A1] study aims to analyze the model of post-rehabilitation psychological assistance for children with narcotic addiction in relation to the principle of child protection. The main problem studied is the limited legal regulation regarding post-rehabilitation assistance, even though this phase is crucial in supporting sustainable recovery and preventing recurrence. The research uses normative juridical methods with a legislative and conceptual approach through literature review of primary and secondary legal materials. The results of the study show that although Law Number 35 of 2009 concerning Narcotics and Law Number 35 of 2014 concerning Child Protection have provided a legal basis for rehabilitation, they have not specifically regulated the mechanism of post-rehabilitation assistance. The community-based psychological mentoring model is seen as effective because it emphasizes the involvement of families, rehabilitation institutions, and the community in creating a safe, inclusive, and stigma-free environment for children. Thus, it is necessary to strengthen regulations and continuous monitoring systems to ensure that the process of social reintegration of children proceeds optimally in accordance with the principles of child protection and the best interests of children.